(untitled) (Applied Biological Research, 2018)
Nineteen commercial cultivars of flax (Linum usitatissimum L.) were subjected to genetic diversity analysis, fingerprinting and identification of informative marker allele(s) for seed purity assessment based on agro-morphological and biochemical quality traits and inter simple sequence repeat (ISSR) marker. A total of 74 reproducible bands ranged from 120 to 1200 bp were amplified out of which 68 were polymorphic among the cultivars. Dendrogram constructed showed no clear grouping of cultivars with regard to the parentage/pedigree record and breeding centres. The 2D plot obtained with PCA analysis clearly supported the results obtained by cluster analysis. Further, ISSR profiling helped in the identification of 15 genotypes by cultivar specific bands. The findings of this study would provide a useful guide for selecting specific cultivar with a desirable agronomic trait with distinct genetic background for linseed breeding program in India.